Measuring of leaf litter decomposition rate and flux of carbon dioxide in various land cover in Gunung Bromo Education Forest, Karanganyar. Issue 1 (July 2021) - Darmawan, A A; Ariyanto, D P; Basuki, T M; Syamsiyah, J
Abstract: The process of leaf litter decomposition on the soil surface as a source of nutrition and food for soil fauna. Leaf litter decomposition rate is influenced by the activity of soil fauna, which is thought to increase the emission of carbondioxide from the soil. The aim of this research was to investigate the leaf decomposition rate and flux of carbon dioxide in various land cover. The research was conducted from July to November 2020 in Gunung Bromo Education Forest, Karanganyar, Central Java. This research used purposive sampling with nine land covers and three replications. The leaf decomposition rate was measured using the litterbag method, and flux of carbon dioxide was measured using the closed chamber method. The results suggested that the leaf decomposition rate was the fastest in Pine 2016 at 6.17 g/week, and the highest flux of carbon dioxide in Indonesian rosewood ( Dalbergia sissoo ) rejuvenation was 9, 860 mg/CO2 /day. The leaf decomposition rate was influenced by air temperature (p = 0.535) compared to humidity (p = - 0.257). Flux carbondioxide is influenced by air temperature (p = 0.854) compared to humidity (p = - 0.677), and the leaf decomposition rate affects the level of flux of carbon dioxide (p = 0.631).